A framework for the design and implementation of competency-based teacher education programmes at the University of Namibia - Engelbrecht, Frederik Daniel Jacobus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Curriculum Studies))--University of Stellenbosch, 2007.